Geriatric ophthalmologic co-management: A case report of interdisciplinary collaboration Geriatrisch-ophthalmologisches Co-Management: Ein Fallbeispiel interdisziplinärer Zusammenarbeit - Krohn, Jan Niklas; Almaqadma, Mohammed; Schmidbauer, Josef; Gosch, Markus; Singler, Katrin (Zeitschrift für Gerontologie und Geriatrie, 2024)
This case report details the assessment and interdisciplinary collaboration in the management of an 81-year-old patient presenting with acute visual impairment, dizziness, general weakness, gait disturbances and fear of falling. A holistic geriatric evaluation revealed orthostatic dysregulation and an underlying multifactorial gait disorder exacerbated by visual impairment. Ophthalmological findings included left central retinal artery branch occlusion and cataracts. A comprehensive geriatric assessment showed frailty, impaired mobility and decreased functional abilities. Subsequent patient-centered interdisciplinary approaches included treatment for retinal ischemia, orthostatic testing, medication reconciliation, physiotherapy and occupational therapy. This case emphasizes how interdisciplinary collaboration between ophthalmology and geriatrics enables proactive assessment and intervention to reduce the risk of functional decline and loss of autonomy in visually impaired patients, which is of particular relevance considering the increasing prevalence of visual impairment in the ageing population.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Activities of daily living; Geriatrics; Interprofessional relations; Occupational therapy; Ophthalmology; Visual impairment